Efficacy and safety of ondansetron orally soluble pellicle for preventing moderate- to high-emetic risk chemotherapy-induced nausea and vomiting - Lu Sun; Jia Ma; Yajuan Zhou; Xiaofang Ying; Gai Liang; Guoliang Pi; Ying Li; Yan Luo; Jianping Bi; Hanping He; Yi Peng (BMC Cancer)
Abstract Objective Ondansetron orally soluble pellicle can serve as an alternative option for preventing nausea and vomiting in patients who receive chemotherapy. However, there is a lack of clinical evidence regarding ondansetron. This study aimed to explore the efficacy and safety of ondansetron in patients with malignant tumours who received chemotherapy drugs with a moderate-to-high emetic risk. Methods In total, 163 patients with malignant tumours received 24 mg of ondansetron via orally soluble pellicles at 30 min before chemotherapy (8 mg each time for three consecutive administrations). The incidence rates of nausea and vomiting in the three days after chemotherapy were recorded. Results Regarding the effect of ondansetron on vomiting, the complete response (zero episodes of vomiting), major response (1–2 episodes of vomiting), minor response (3–5 episodes of vomiting), and failure (> 5 episodes of vomiting) rates were 96.9%, 1.2%, 1.2%, and 0%, respectively. The major efficacy rate for vomiting (complete response + major response rates) was 98.1%. Moreover, 96.3% of patients did not experience nausea, 2.5% of patients experienced mild nausea, 1.2% of patients experienced moderate nausea, and 0.0% of patients experienced severe nausea. The major efficacy rate for nausea (no nausea) was 96.3%. Age > 65 years was negatively associated with major efficacy for vomiting, and a chemotherapy regimen involving cisplatin was negatively associated with major efficacy for nausea. A total of 42 (25.8%) patients experienced adverse events. The most common adverse events were elevated levels of alanine transaminase (6.7%), elevated levels of aspartate transaminase (3.7%), fatigue (3.7%), and cough (2.5%). Conclusion Ondansetron orally soluble pellicle shows good antiemetic efficacy and high safety in patients with malignant tumours who receive chemotherapy drugs with a moderate-to-high emetic risk.